Farm Soil Testing Techniques, Soil Health, and Potential Impact of Artificial Intelligence as Factors of Small-Scale Farming Soil Management - Louiella Samaniego Ann; Gallego Marianito (E3S Web of Conferences)
Small-scale farming is vital to global food production, especially in rural communities that may face constraints in resource availability and technology access. This study, conducted in the first quarter of the 2024 in the CALABARZON region (Cavite, Laguna, Batangas, Rizal, and Quezon Province) of the Philippines, investigates soil management practices among small-scale farmers engaged in subsistence and semi-commercial agriculture. It assesses farm soil testing techniques, current soil health, farmers’ awareness of Artificial Intelligence (AI) applications and its potential impact on soil management. The study uses a stratified sampling approach to analyze challenges from 103 farmers, with the survey data examined through descriptive and inferential statistics. The findings reveal that small-scale farmers exhibit hesitancy towards soil testing and adopting technological advancements like AI, primarily due to limited knowledge and financial constraints, hindering their ability to address soil health issues and improve management practices, despite recognizing potential benefits. This study offers valuable insights and benefits for small-scale farmers aiming to implement technological applications for their farms and address soil health issues in their management practices.